A novel PWM technique for reduced switch count multilevel inverter in renewable power applications - Rakesh Shriwastava; Sonali Gosavi; Shridhar S. Khule; Somnath Hadpe; Mohan P. Thakare (Institute of Advanced Engineering and Science, 2023)
This paper described a novel pulse width modulation (PWM) technique in reduced switch count multilevel inverter (MLI) for renewable power applications. Therefore, the proposed technique finds a better solution in the multilevel inverters used for improving power quality, efficiency and reduction of switching and conduction losses. It produces a smoother sinusoidal output waveform with reduced total harmonic distortion (THD) using different modulation technique. The novel PWM technique consists of nearest level control (NLC) and level shift pulse width modulation (LSPWM). Normally semiconducting devices are added for increasing number of levels. It affects the power quality and efficiency due to losses. In this work, MLI topology with reduced number of switches count for NLC and LSPWM is presented. The single-phase and three-phase inverter configuration is used in proposed mythology. Detailed simulation results for 7-level inverter of single and three-phase inverters are presented in this paper. It is observed that NLC method is better efficiency and reduced THD than LSPWM for better utilization in renewable power applications.